Modeling Sustainable Manufacturing Practices Towards Economy Sustainability Performance - Abu, Nor Hashidah; Mohamad Jaya, Abdul Syukor; Muhamad, Mohd Razali (Asian Research Publishing Network (ARPN), 2017)
The purpose of this study is to present relationship between sustainable manufacturing practices (SMP) and economy sustainability performance (SP1_Economy). Eight practices that may affect SP1_Economy were studied. In the first phase, a multiple regression model considered a linear relationship between eight variables and SP1_Economy as performance was considered to the best fit of the observed values. It was perceived that multiple linear regression method indicated 24% from SP1_Economy of the variation in the observed data. Finally, it can be conclude that multiple linear regression method can predict the performance from observed practices in manufacturing firms.